Literackie kreacje przeszłości w nurcie kryminału retro na przełomie XX i XXI wieku = Literary creations of the past in vintage crime fiction at the turn of the 20th and 21st centuries - Mazurkiewicz, Adam (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
In the case of vintage crime fiction, the blurred affiliation to different cultural circulations derives from the problematisation of the image of the past employed in the construction of the nar?ration. It cannot be considered within one of the two domineering artistic strategies typical for the description of the "past events": apologetic or revisionist, both sharing the conviction that the cultural memory of a reader must be somehow altered. Thus, it is not without importance what readers of "vintage" crime fiction - as the consumers of cultural goods - really remember, how they do it, and most importantly - what is the purpose of the remembering.
Keywords: literatura kryminalna; pamięć; historia; przeszłość; crime fiction; memory; history; past